Comparing the trends of cancer burden attributed to high BMI in China and globally from 1990 to 2021, with multi-model prediction to 2036 - Chen, Nanting; Xing, Lingzhi; Xiang, Fengyun; Li, Chengmiao; Li, Letai; Cheng, Jingsong; Yu, Yangfan; Gong, Yubowen; Liu, Xiao; Xie, Fangjiao; Chen, Ling (Frontiers in Public Health, 2025)
IntroductionHigh body mass index (BMI) has been identified as a significant contributor to cancers. However, details regarding the evolution of the cancer burden attributable to high BMI in China have not been available. With the epidemic of high BMI among Chinese recent years, it's essential to evaluate the disease burden of cancer associated with high BMI to guide disease interventions and enhance public health. This study aimed to evaluate the burden of high BMI-attributed cancer in China from 1990 to 2021 and compare it with global trends.MethodsThe temporal trends of high BMI-attributed cancer were assessed using annual percentage change (APC) and overall percentage change. Decomposition and age-period-cohort analyses were conducted to identify influential factors, while future trends were projected with the Bayesian age-period-cohort (BAPC), auto-regressive moving average model (ARIMA), and exponential smoothing model (ETS).ResultsIn China, the age-standardized mortality rate (ASMR) and age-standardized disability-adjusted life-years rate (ASDR) for high BMI-attributed cancer increased to 2.81 (95% UI: 1.20–4.76)/105 and 79.17 (95% UI: 33.82–134.14)/105 in 2021, remaining below the global average. While the APC of ASMR and ASDR constantly increased in China, global trends exhibited minimal change. Colorectal and liver cancers were the most prevalent types of high BMI-attributed cancer. In China, the period and cohort effects on high BMI-attributed cancer increased more significantly, with the age effect showing an exponential rise. Aging accounted for 43.92% of high BMI-attributed cancer related deaths and 40.03% of disability-adjusted life-years (DALYs) in China. Over the next 15 years, the burden of high BMI-attributed cancer in China would show a more significant upward trend compared with global trends.ConclusionsAlthough China's current high BMI-attributed cancer burden remains below the global average, it is increasing at a substantial rate and is expected to continue increasing rapidly. Targeted prevention strategies tailored to age and the latest high BMI-attributed cancer spectrum are urgently needed to mitigate this growing public health concern in China.